A revolution in military learning? Cross-functional teams and knowledge transformation by lessons-learned processes. Issue 4 (1st October 2020) - Dyson, Tom
ABSTRACT: The post-Cold War era has witnessed the widespread development of lessons-learned processes within NATO member-states. However, practitioner guidance and military innovation studies are yet to properly investigate the insights of management studies about best-practice in lessons-learned processes. In particular, they have failed to identify the activities which enable militaries to "transform" knowledge, by effectively combining new knowledge with existing organisational knowledge. Drawing upon the academic literature on cross-functional teams and original interview research, this article examines the organisational activities which improve the crucial "remedial action" phase of lessons-learned processes. It breaks new ground by identifying six key dimensions of lessons-learned process cross-functional teams and the organisational activities which enhance their performance. In doing so, the article improves understanding about the team processes and wider organisational activities which shape lessons-learned process effectiveness. It also examines the challenges associated with encouraging well-informed oversight of lessons-learned processes by the civilian and military leadership. The article concludes by identifying a number of important research agendas on lessons-learned processes.